Sosialisasi Kewirausahaan Sosial untuk Anggota Majelis Ta’lim Baitturahman Cipete Selatan - Soeratin, Harry Zacharias; Kusuma, Airlangga Surya; Handoko, Irfan; Priambodo, Ary; Adams, Ravi (Jurnal Pustaka Dianmas, 2025)
This community service activity aims to enhance the understanding and awareness of the Majelis Ta’lim Baitturahman Cipete Selatan members regarding the concept and implementation of social entrepreneurship. Social entrepreneurship is a strategic approach to strengthening community economic independence and promoting sustainable social welfare. The activity was conducted on Wednesday, November 26, 2025, at the Majelis Ta’lim Baitturahman Hall, South Cipete, South Jakarta, with 20 participants. The implementation used a participatory approach involving interactive lectures, group discussions, and a simulation of community-based social business model design. The materials were developed based on a value-based social entrepreneurship framework. The results revealed that the participants gained a deeper understanding of the importance of integrating spiritual, social, and economic values into social entrepreneurship practices. Participants also identified potential social enterprises within their communities, such as culinary businesses, handicraft production, and digital skills training. This program demonstrates that religious institutions, such as Majelis Ta’lim, can serve as agents of social transformation through productive economic activities rooted in Islamic values and communal benefits.